2009
DOI: 10.1109/tase.2008.917140
|View full text |Cite
|
Sign up to set email alerts
|

Regularity Analysis for Patterned Texture Inspection

Abstract: This paper considers regularity analysis for patterned texture material inspection. Patterned texture-like fabric is built on a repetitive unit of a pattern. Regularity is one of the most important features in many textures. In this paper, a new patterned texture inspection approach called the regular bands (RB) method is described. First, the properties of textures and the meaning of regularity measurements are presented. Next, traditional regularity analysis for patterned textures is introduced. Many traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 26 publications
0
60
0
Order By: Relevance
“…Methods that are found in literature for the inspection of patterned texture images include the traditional image subtraction methods [10][11][12], the method of golden image subtraction (GIS) [5], the method of wavelet-preprocessed golden image subtraction (WGIS) [5], the method of Direct-Thresholding (DT) based on wavelet transform [5], the Bollinger Bands method [6], the Regular Bands method [3], the Local Binary Pattern (LBP) method [7], and the motif-based methods [4,8,9].…”
Section: Previous Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Methods that are found in literature for the inspection of patterned texture images include the traditional image subtraction methods [10][11][12], the method of golden image subtraction (GIS) [5], the method of wavelet-preprocessed golden image subtraction (WGIS) [5], the method of Direct-Thresholding (DT) based on wavelet transform [5], the Bollinger Bands method [6], the Regular Bands method [3], the Local Binary Pattern (LBP) method [7], and the motif-based methods [4,8,9].…”
Section: Previous Methodsmentioning
confidence: 99%
“…This was done with the help of the moving average and standard deviation [3]. Thresholds obtained from several histogram-equalized defect-free images during the training stage were used for detecting defects on histogram-equalized defective images during the testing stage.…”
Section: Previous Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Grigorescu and Petkov [3], determine texel size of periodic and near-periodic images based on the calculation of Renyi's generalized entropies by assuming a square texel for all textures. Other studies for texture periodicity detection are found in the literature, we can mention those based on the wavelet transform [8], autocorrelation [10,9], or regular bands [15].…”
Section: Introductionmentioning
confidence: 99%